Genetic Approaches Reveal a Non-Hormonal Etiology for Hyperemesis Gravidarum [7L]. (May 2017) - Fejzo, Marlena S.; MacGibbon, Kimber W.; Schoenberg, Frederic P.; Sazonova, Olga; Vacic, Vladimir; Mullin, Patrick
Abstract : INTRODUCTION: While very common, the cause of nausea and vomiting in pregnancy (NVP) remains elusive. Evidence suggests a genetic predisposition to the most severe form of NVP, hyperemesis gravidarum (HG). An understanding of the molecular mechanism behind HG will lead to targeted therapies to predict, diagnose, treat, and even prevent HG. METHODS: Using a novel approach to study NVP, we performed both a genome-wide association study (GWAS) on 1, 306 cases with HG treated with intravenous fluids and 15, 766 cases without NVP, and a whole-exome sequencing (WES) study of five families with HG to identify common and rare predisposing genes. RESULTS: WES identified RYR2, an intracellular calcium release channel that signals vomiting. GWAS identified a gene in the same pathway as RYR2 as well as genes that appear to play major roles in pregnancy and nausea. Neither method identified mutations or associations between HG and pregnancy hormones. CONCLUSION: This study suggests a possible paradigm shift away from a hormonal etiology for NVP. The genes linked to HG play roles in pregnancy and in nausea and vomiting. Treatments that affect some of these new targets are already under investigation. New avenues for prediction, diagnosis, and treatment should follow.